Opinions and Perceptions of Bank Managers on the Quality of Provisions of Internet Banking Services - Bucur, Luiza Emanuela; Manea, Natalia; Goldbach, Dumitru (Journal of Economic Development, Environment and People, 2019)
Following the accession of Romania to the European Union, the services sector has made important progress. Currently, this sector exceeds 50% of Romania's GDP. Banking has an important role in the economy by making financial intermediation, attracting deposits and placing credits. The increase in the number of banks on the Romanian market has led to intensification of competition and especially the awareness of the quality of online banking services offered. Therefore, the bank management has to take into account not only the” quality desired or achieved by the bank”, but also the quality perceived by the customer. In this paper we will start with an introduction of bank sector, then the we will present the methodology of research. The design of interview guide is the next step and in the main part of the paper is the analyses of data obtained and interpretation of results.